Global warming and the American economy a regional assessment of climate change impacts - Mendelsohn, Robert O., 1952-; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2001)
The impact of climate change on seven regions of the United States is studied in this new and accessible collection. The study examines how the different regions of the United States may be affected by climate change. In particular, the study explores whether warming would be beneficial to the northern (colder) regions but harmful to the economies of the southern (warmer) regions.
1. Introduction -- 2. Agriculture : agronomic-economic analysis -- 3. Agriculture : a Ricardian analysis -- 4. Timber : ecological-economic analysis -- 5. Water resources : economic analysis -- 6. Coastal structures : dynamic economic modeling -- 7. Energy : cross-sectional analysis -- 8. Adaption -- 9. Synthesis.
"In association with the Electric Power Research Institute."
Includes bibliographical references and index.
Keywords: Climatic changes -- United States; United States -- Economic conditions -- 1981-2001 -- Regional disparities; Electronic books